Association of lung health and cardiovascular health (Life’s Essential 8) - Zhang, Wanjia; Zou, Menglong; Liang, Junyao; Zhang, Dexu; Zhou, Man; Feng, Hui; Tang, Chusen; Xiao, Jie; Yi, Zhan; Xu, Yin (Frontiers in Medicine, 2025)
BackgroundCardiorespiratory health issues often intersect. This study explored the relationship between lung health and the recently updated Cardiovascular Health Measure (Life’s Essential 8).MethodsData from the 2007–2018 National Health and Nutrition Examination Survey (NHANES) were analyzed. Three cohorts were included: lung disease in the Main cohort (N = 9,772), lung function in the Spirometry sub-cohort (N = 3,896), and respiratory symptoms in the Respiratory Symptoms sub-cohort (Age > 40) (N = 3,449). LE8 scores were used as both continuous and categorical variables (0–49, 50–79, 80–100). Weighted multivariate regression analyses examined the correlations between LE8 and lung health, and weighted restricted cubic spline (RCS) regression analyzed potential non-linear relationships. Subgroup analysis was conducted to verify stability.ResultsOverall lung health was better in the high LE8 group than in the low LE8 group. In the fully adjusted model, the high LE8 group had significantly lower odds of asthma (OR = 0.42; 95% CI = 0.29, 0.59) and chronic bronchitis (OR = 0.27; 95% CI = 0.15, 0.49) compared to the low LE8 group. Regarding lung function, each 10-point increase in LE8 was associated with an increase of 50 ml in FEV1 (Beta = 50; 95% CI = 32, 67) and 56 ml in FVC (Beta = 56; 95% CI = 32, 79). Among middle-aged and older adults (age > 40), the high LE8 group had significantly lower odds of respiratory symptoms, including cough (OR = 0.23; 95% CI = 0.12, 0.46), phlegm (OR = 0.42; 95% CI = 0.19, 0.90), and wheezing (OR = 0.29; 95% CI = 0.15, 0.54). RCS analyses demonstrated a non-linear negative correlation between LE8 and cough, sputum, and wheeze. Subgroup and sensitivity analysis suggested stability.ConclusionLife’s Essential 8 (LE8) scores are positively associated with lung health in the US population. These findings provide a valuable reference for maintaining overall cardiorespiratory health.